2022
DOI: 10.1038/s41467-022-30092-2
|View full text |Cite
|
Sign up to set email alerts
|

Type II porous ionic liquid based on metal-organic cages that enables l-tryptophan identification

Abstract: Porous liquids with chemical separation properties are quite well-studied in general, but there is only a handful of reports in the context of identification and separation of non-gaseous molecules. Herein, we report a Type II porous ionic liquid composed of coordination cages that exhibits exceptional selectivity towards l-tryptophan (l-Trp) over other aromatic amino acids. A previously known class of anionic organic–inorganic hybrid doughnut-like cage (HD) is dissolved in trihexyltetradecylphosphonium chlori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…By using the IGMH analysis, the intermolecular interaction between DMMP and MOF-808 was clarified and found to be van der Waals interaction predominantly in Fig. 4g (blue denoted strong attractions including hydrogen bond, green indicated van der Waals interaction, and yellow represented strong repulsion including steric hindrance) 54 . The amorphous SiO 2 has previously been regarded as a suitable adsorbent for chemical warfare agents due to the reliable affinity and stability of the resultant complex 55,56 .…”
Section: Dmmp Adsorption and Degradationmentioning
confidence: 99%
“…By using the IGMH analysis, the intermolecular interaction between DMMP and MOF-808 was clarified and found to be van der Waals interaction predominantly in Fig. 4g (blue denoted strong attractions including hydrogen bond, green indicated van der Waals interaction, and yellow represented strong repulsion including steric hindrance) 54 . The amorphous SiO 2 has previously been regarded as a suitable adsorbent for chemical warfare agents due to the reliable affinity and stability of the resultant complex 55,56 .…”
Section: Dmmp Adsorption and Degradationmentioning
confidence: 99%
“…12,13 Thereafter a simpler way is developed to dissolve or disperse the intrinsically porous hosts in bulky solvents that are sterically prevented from entering the host cavity. 16−18 The resulting solutions 19,20 and suspensions, 21,22 which are called type II and III PLs, consist of permanent pores that are accessible to gas molecules for consequent gas sorption applications. 23 ments, the fluid nature of all PLs can cause difficulties in some practical cases such as solution/suspension stability, packaging, leakage, and portability, which restricts their further use, especially in applications requiring a stable shape.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recent works have shown that persistent cavities can be engineered into liquids to endow the so-called porous liquids (PLs) with intrinsic permanent microporosity. The technical challenge associated with PL synthesis is the creation of permanent pores, which are not occupied by the liquid components (Figure a) . The preliminary idea is to synthesize liquid molecules consisting of unoccupied pores to obtain type I PLs, which require complicated and costly molecular synthesis to endow fluidity. , Thereafter a simpler way is developed to dissolve or disperse the intrinsically porous hosts in bulky solvents that are sterically prevented from entering the host cavity. The resulting solutions , and suspensions, , which are called type II and III PLs, consist of permanent pores that are accessible to gas molecules for consequent gas sorption applications . Despite the achievements, the fluid nature of all PLs can cause difficulties in some practical cases such as solution/suspension stability, packaging, leakage, and portability, which restricts their further use, especially in applications requiring a stable shape …”
Section: Introductionmentioning
confidence: 99%
“…Porous liquids (PLs), which were first proposed by James, have garnered significant attention due to their favorable fluidity and permanent, well-defined molecule-sized pores. These liquids can be classified into three main categories: Type I PLs are neat liquids that cannot collapse or interpenetrate, , which are created by modifying porous cores with long chains, such as silica nanoparticles and metal–organic frameworks (MOFs). Type II PLs consist of rigid hosts that dissolve in solvents that are too sterically hindered to occupy the cavities. Porous organic cages (POCs), metal–organic polymers (MOPs), and metal–organic cages are typical cores of type II porous liquids. Finally, type III PLs include nanoparticles of MOFs and zeolites that disperse in sterically hindered solvents. …”
Section: Introductionmentioning
confidence: 99%